AN EQUATION FOR ESTIMATING THE (R) USLE SLOPE STEEPNESS FACTOR, S - Mulengera, Matthew K (Tanzania Journal of Engineering and Technology, 2017)
Currently three equations are used for calculating slope steepness factor for the revised universal soil loss equation (RUSLE); one for slopes less than nine percent, the second for slopes equal or greater than nine percent, and the third equation that has been proposed for use in China for slopes equal or greater than 17 %. The three equations have linear relationships between slope steepness factor, S and the sine of the slope angle, q. The three equations under predict the factor, S when used on slope steepness beyond the data sets used to develop them. In addressing this problem several alternative forms of equations (linear, power, and polynomial) were tested using field plot soil loss data gathered by several researchers in different countries for slopes ranging from three percent to 55 %. A single power function relating the sine of the slope angle, q to the slope steepness factor, S has been identified to be more suitable and accurate for estimating the RUSLE slope steepness factor, S.